Carrier extraction from metallic perovskite oxide nanoparticles. Issue 28 (9th July 2021) - McDonald, Calum; Ni, Chengsheng; Švrček, Vladimir; Macias-Montero, Manuel; Velusamy, Tamilselvan; Connor, Paul A.; Maguire, Paul; Irvine, John T. S.; Mariotti, Davide
Abstract : We observe the extraction of carriers excited between two types of bands in the perovskite oxide, Sr-deficient strontium niobate (Sr0.9 NbO3 ). Abstract : We observe the extraction of carriers excited between two types of bands in the perovskite oxide, Sr-deficient strontium niobate (Sr0.9 NbO3 ). Sr0.9 NbO3 exhibits metallic behaviour and high conductivity, whilst also displaying broad absorption across the ultraviolet, visible, and near-infrared spectral regions, making it an attractive material for solar energy conversion. Furthermore, the optoelectronic properties of strontium niobate can easily be tuned by varying the Sr fraction or through doping. Sr-deficient strontium niobate exhibits a split conduction band, which enables two types of optical transitions: intraband and interband. However, whether such carriers can be extracted from an unusual material as such remains unproven. In this report, we have overcome the immense challenge of photocarrier extraction by fabricating an extremely thin absorber layer of Sr0.9 NbO3 nanoparticles. These findings open up great opportunities to harvest a very broad solar spectral absorption range with reduced recombination losses.